Real-world patient characteristics and survival outcomes in patients with advanced or recurrent endometrial cancer in England: a retrospective, population-based study - Clare Pearson; Susana Banerjee; Kiera Heffernan; Tameera Rahman; Jamie Garside; Alvaro Ingles Russo Garces (BMJ Open)
Objective This study defined a retrospective cohort of patients in England with primary advanced or recurrent (A/R) endometrial cancer (EC) who may have been eligible for clinical trials evaluating immune checkpoint inhibitors (ICIs) in the first-line (1L) setting within a real-world dataset, and described the characteristics, treatment patterns and outcomes within this cohort.Design This was a retrospective, population-based study.Setting Routine population-level data from the National Cancer Registration and Analysis Service in England were used. Patients diagnosed with A/R EC between 1 January 2013 and 31 December 2019 were included (follow-up until 23 August 2021). ICI-eligible patients who received any 1L therapy (defined as first systemic treatment for A/R EC with or without radiotherapy) and met key eligibility criteria for the RUBY trial (NCT03981796; 1L cohort) were included. A subpopulation who solely received carboplatin–paclitaxel at 1L (carboplatin–paclitaxel subcohort) was identified.Methods Demographics, characteristics and therapy received were reported. Overall survival (OS), time to next treatment (TTNT) and time to treatment discontinuation (TTD) from 1L chemotherapy initiation were assessed using Kaplan-Meier methodology.Results Of 13 954 patients identified, 2376 ICI-eligible patients were included in the 1L cohort (median [range] age: 67.9 [26.7–94.0] years); 902 patients received solely carboplatin–paclitaxel at 1L. Demographics and disease characteristics were generally similar between cohorts. Median (95% CI) OS, TTNT and TTD from 1L chemotherapy were 27.2 (24.7, 30.2), 16.9 (15.8, 18.5) and 3.4 (3.4, 3.4) months, respectively, in the 1L cohort, and 17.2 (15.5, 19.0), 12.4 (11.6, 13.5) and 3.4 (3.4, 3.4) months, respectively, in the carboplatin–paclitaxel subcohort.Conclusion Long-term outcomes were poor for both cohorts, particularly the carboplatin–paclitaxel subcohort, where patients did not receive radiotherapy and had predominantly metastatic disease. This reflects the unmet need for more durable treatment options to prevent relapse and prolong survival in this patient population. This real-world study will help contextualise outcomes from ongoing phase III clinical trials investigating 1L ICI treatments.